The Human Cytomegalovirus (HCMV) Tegument Protein UL94 Is Essential for Secondary Envelopment of HCMV Virions - Phillips, Stacia L. (American Society for Microbiology, 2012)
Human cytomegalovirus (HCMV) virions are structurally complex, and the mechanisms by which they are assembled are poorly understood. However, several tegument proteins are known to be essential for proper particle assembly and maturation. Despite intense investigation, the function of many tegument proteins remains unknown. The HCMV UL94 gene is conserved among all herpesviruses and encodes a virion protein of unknown function. We demonstrate here that UL94 is a tegument protein that is expressed with true-late kinetics and localizes to the viral assembly complex during infection. To elucidate the function of UL94, we constructed a UL94-null mutant, designated UL94stop. This mutant is completely defective for replication, demonstrating that UL94 is essential. Phenotypic analysis of the UL94stop mutant shows that in the absence of UL94, viral gene expression and genome synthesis occur at wild-type levels. However, analysis of the localization of viral proteins to the cytoplasmic assembly complex shows that the essential tegument protein UL99 (pp28) exhibits aberrant localization in cells infected with the UL94stop mutant. Finally, we show that there is a complete block in secondary envelopment in the absence of UL94. Taken together, our data suggest that UL94 functions late in infection to direct UL99 to the assembly complex, thereby facilitating secondary envelopment of virions.